Missense mutation of SERPINC1 (p.Ser426Leu) in a young patient presenting as refractory and recurrent venous thromboembolism: A case report - Yu, Haixu; Gai, Xiaoyan; Wang, Jianli; Zhuang, Jinman; Guo, Wanwan; Qiao, Rui; Zhu, Hong; Sun, Yongchang (Frontiers in Cardiovascular Medicine, 2022)
Genetic and acquired risk factors are extremely important mechanisms in the development of venous thromboembolism (VTE). Inherited antithrombin (AT) deficiency due to mutations in the SERPINC1 gene is a well-known risk factor for genetic thrombophilia. In this case, we reported a 28-year young abroad student who presented with refractory and recurrent VTE in-hospital. This patient presented with a 2-month history of right lower limb pain and 1 week of fever. The ultrasound showed deep venous thrombosis in the right common and superficial femoral veins. The CTPA confirmed acute pulmonary embolism with multiple filling defects in both pulmonary arteries. He was diagnosed with "pulmonary embolism, pneumonia, lower extremity venous thrombosis". The level of serum antithrombin was normal, yet gene sequencing revealed a heterozygous missense mutation of SERPINC1, c.1277C>T (p.Ser426Leu). The patient underwent anticoagulant therapy of heparin and inferior vena cava filter implantation. The patient had undergone recurrent VTE despite adequate anticoagulation with heparin during the first 2 weeks. The swelling, pain, and thrombosis of lower extremity veins got resolved from warfarin and rivaroxaban. Inherited antithrombin deficiency due to mutations in the SERPINC1 gene is the genetic basis of this patient, and warfarin/rivaroxaban, other than heparin, is beneficial.